IDENTIFIKASI DIMENSI BIOLOGI GURITA DI PANTAI KETAPANG LOMBOK TIMUR UNTUK PENGELOLAAN PERIKANAN BERKELANJUTAN - DAMAI DINIARIWISAN; MUHAMMAD MARZUKI; WIWID ANDRIYANI LESTARININGSIH (Universitas Mahasaraswati K. Mataram, 2023)
Octopus is a mollusk which has high economic value. Ketapang Beach in East Lombok Regency is one of the octopus landing locations, so it is necessary to know the current conditions of the biological dimensions of octopuses, such as growth patterns, body shape, age group, catchability and spawning for sustainable octopus management. The purpose of this study was to find out the current condition of the octopus fishery sector, especially the biological dimension. The research uses a descriptive survey method, data and information comes from a population sample to describe objects according to actual conditions, then processed using regression. The research results stated that the growth pattern of octopuses landed on Ketapang Beach was negative allometric, where the b value was 5.161 (b>3), where the weight growth was greater than the increase in body length. The age group values at the location are dominated by octopuses of the adult age group with the highest coat length value > 12 cm with 38 individuals, and supported by 45 mature octopuses of which 38 individuals (76%) have PM > 12 cm, and 7 individuals (14 %) have PM 9 – 11 cm